Peran Guru Pendidikan Agama Kristen Dalam Memanfaatkan Norma Sosial Sebagai Upaya Membangun Karakter Siswa SDN 064959 Medan Area - Marpaulina Simamora (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
In the context of education, Christian Religious Education (PAK) teachers not only function as teachers, but also as moral role models who teach Christian values ​​and social norms that are important for the development of students' character. This study aims to examine the role of Christian Religious Education (PAK) teachers based on social norms in building student character at SDN 064959 Medan Area. This study uses a qualitative literature method by collecting data from observations, interviews, and relevant literature studies. The results of the study indicate that PAK teachers play a role in instilling Christian values ​​that teach social norms to maintain tolerance in living together with others. PAK teachers also function as facilitators in creating a learning environment that supports the development of empathy and social concern among students. This study emphasizes that Christian religious education has a significant impact on forming individuals who are not only knowledgeable, but also have strong moral and ethical integrity. The conclusion in this study provides insight into the development of a Christian religious education curriculum that is more effective and relevant to the needs of today's society.